SCHOOL LITERATION IN SHAPING THE CHARACTER OF STUDENTS - Yuliana Nanda Sari; Ahmad Hariandi; Dwi Rahmadini; Erlina Dwi Saputri; Yeni Wahyuningsih (AL-ISHLAH: Jurnal Pendidikan, 2020)
The purpose of this study is to review and explain the role of school literation in shaping the character of the learner especially in class II in elementary school. The research method used in this study is a qualitative approach with the type of phenomenological research. The findings obtained in the field were obstacles in the application of this literacy movement, namely that the student focus was easily lost, so they were playing around and it disturbed their friends who wanted to focus on reading. The results of this study shows that the existence of 15 minutes of reading before the lesson begins, the existence of a varied collection of books, reading activities carried out every day and literacy activities at school can foster student’s enthusiasm for reading which is decreasing day by day due to the influence of gadget and the environment of students who do not care about the importance of reading. The conclusion of this research can be concluded that: 1) The application of the literacy culture in school at SDN 111/I Muara Bulian is categorized as quite good, 2) the application of a school literacy culture, it can form the character of students by respecting people who speak, respecting each other and older people